Supported Liquid Membrane With Selective Stripping For Separative Recovery Of Copper And Zinc From Multimetal Wastewater - Goh, Saik Su (2024)
In Malaysia, Standards A and B of the Environmental Quality (Industrial Effluent) Regulations 2009 establish effluent limits, including metal concentration thresholds, to regulate emissions of harmful metal pollutants in wastewaters. Treatment is essential to meet these limits before discharging wastewater. Instead of mere removal, metal recovery for recycling offers a more sustainable approach, aligning with circular economy initiatives. Supported liquid membrane (SLM) has been viewed as a potential alternative. In SLM, specific settings are required for selective metal transport and recovery. Under some conditions, selective transport is not possible due to multiple metal coextraction by the carrier used in SLM. As an alternative to using multiple SLM settings and to overcome metal coextraction, this study aimed to investigate the utilization of strip dispersion with selective stripping in a single-carrier SLM system for separative recovery of copper and zinc. Di-(2- ethylhexyl)phosphoric acid (D2EHPA) diluted by kerosene was used as the membrane phase.